DECENTRALIZED WASTEWATER TREATMENT: AN INNOVATIVE APPROACH FOR RURAL AREAS - Bartula, Mirjana; Bartula, Mirjana; Šekler, Ivana; Jeremić , Dragan (Economics of Agriculture, 2025)
This study provides a comparative analysis of conventional and innovative wastewater treatment technologies for small settlements of up to 2,000 equivalent inhabitants (EH). Conventional systems such as the Sequencing Batch Reactor (SBR), Membrane Bioreactor (MBR), and Moving Bed Bioreactor (MBBR) were evaluated based on treatment efficiency, energy consumption, sludge production, operational complexity, and spatial requirements. Additionally, the potential of phytoremediation, specifically constructed wetlands, as a sustainable and low-cost alternative was explored. The study concludes that phytoremediation systems are a viable option for decentralized wastewater treatment in rural or ecologically sensitive areas due to their low operational costs and minimal energy needs. It recommends wider adoption of these systems, supported by further research and educational programs to optimize their design across different climates.